How can we engage farmers in bioenergy development? Building a social innovation strategy for rice straw bioenergy in the Philippines and Vietnam - Minas, Angela Mae; Mander, Sarah; McLachlan, Carly (Elsevier, 2020)
Involving farmers and local communities in bioenergy development is important for the deployment of sustainable bioenergy systems, especially if rural areas are to maximise potential co-benefits from energy provision. Focusing on rice straw bioenergy in the Philippines and Vietnam, our research explored how farmers’ social networks can serve as a platform for social innovation – an emerging approach to energy transitions aimed at delivering solutions by empowering local people. Specifically, we used tools in social network analysis to map how farmers mobilise resources within their communities, who influences their decisions on the farm, and the stories embedded in their interactions. This allowed us to develop insights on how different actors in farmers’ networks may be best connected to support collaborative partnerships and co-designing of solutions that meet their development needs. Our results showed potential windows of opportunity to engage farmers in bioenergy development. First, by connecting them to resource providers; and second, by developing capacities and network structures in rice farming communities to enable more resource sharing. Based on these, we propose a social innovation strategy useful for bioenergy project developers and local stakeholders to help ensure that farmers and other actors in the community can take active roles in the rice straw bioenergy development process.